2006
DOI: 10.1098/rspb.2006.3740
|View full text |Cite
|
Sign up to set email alerts
|

Condition dependence of reproductive strategy and the benefits of polyandry in a viviparous lizard

Abstract: Species in which males do not contribute to reproduction beyond the provision of sperm offer good opportunities to study the potential genetic benefits that females can obtain from polyandry. Here, we report the results of a study examining the relationships between polyandry and components of female fitness in the common lizard (Lacerta vivipara). We found that polyandrous females produce larger clutches than monandrous females. Polyandrous females also lose fewer offspring during the later stages of gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 51 publications
0
51
0
Order By: Relevance
“…We only considered non-viable offspring when estimating clutch size to avoid a bias with the data coming from autopsied females. Deducing from extensive clutch size data on a Z. vivipara population in southern France (Eizaguirre et al 2007), exclusion of non-viable offspring would result in quite minor decrease (0.07–0.20) of mean values; this bias is negligible as compared to the studied geographic variation (e.g., Orlova et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…We only considered non-viable offspring when estimating clutch size to avoid a bias with the data coming from autopsied females. Deducing from extensive clutch size data on a Z. vivipara population in southern France (Eizaguirre et al 2007), exclusion of non-viable offspring would result in quite minor decrease (0.07–0.20) of mean values; this bias is negligible as compared to the studied geographic variation (e.g., Orlova et al 2005). …”
Section: Methodsmentioning
confidence: 99%
“…1994; Eizaguirre et al. 2007; Noble et al. 2013), only one study thus far has shown that male siring success correlated with the extent of genetic relatedness to the mother (Olsson et al.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, molecular methods of paternity assignment provide an additional source of data on reproductive success, free of many of the biases inherent in behaviour-based measures of male mating success (Eizaguirre et al 2007 …”
Section: Discussionmentioning
confidence: 99%